Q.1 The difference between two whole numbers is . The ratio of the two numbers is . What are the
two number
Q2. Solve: 2y + 9 = 4
Q3. Solve the equation t/5 = 10.
Q4. Solve:
![\frac{5x}{2x - 1} = 2 \frac{5x}{2x - 1} = 2](https://tex.z-dn.net/?f=+%5Cfrac%7B5x%7D%7B2x+-+1%7D++%3D+2)
Q5. Simplify and solve the linear equation 3(t – 3) = 5(2t + 1).
Q6. Solve the equations and check your result: 2x - 1 = 14 - x.
Q7. Solve the equation:
![\frac{9x}{7 - 6x} = 15 \frac{9x}{7 - 6x} = 15](https://tex.z-dn.net/?f=+%5Cfrac%7B9x%7D%7B7+-+6x%7D++%3D+15)
Q8. Solve the equation:
![\frac{8x - 3}{3x} = 2 \frac{8x - 3}{3x} = 2](https://tex.z-dn.net/?f=+%5Cfrac%7B8x+-+3%7D%7B3x%7D++%3D+2)
Q9. Solve the equation and check your result: 4z + 3 = 6 + 2z
Q10. Solve the equation 7x – 9 = 16.
Q11. Solve the linear equation
![\frac{x - 5}{3} = \frac{x - 3}{5} \frac{x - 5}{3} = \frac{x - 3}{5}](https://tex.z-dn.net/?f=+%5Cfrac%7Bx+-+5%7D%7B3%7D++%3D++%5Cfrac%7Bx+-+3%7D%7B5%7D+)
Q12. Solve the linear equation
![x + 7 - \frac{8x}{3} = \frac{17}{6} - \frac{5x}{2} x + 7 - \frac{8x}{3} = \frac{17}{6} - \frac{5x}{2}](https://tex.z-dn.net/?f=x+%2B+7+-++%5Cfrac%7B8x%7D%7B3%7D++%3D++%5Cfrac%7B17%7D%7B6%7D++-++%5Cfrac%7B5x%7D%7B2%7D+)
Q13. Solve the equation
![\frac{3y + 4}{2 - 6y} = \frac{ - 2}{5} \frac{3y + 4}{2 - 6y} = \frac{ - 2}{5}](https://tex.z-dn.net/?f=+%5Cfrac%7B3y+%2B+4%7D%7B2+-+6y%7D++%3D++%5Cfrac%7B+-+2%7D%7B5%7D+)
Q14. Solve the linear equation
![\frac{3t - 2}{4} - \frac{2t + 3}{3} = \frac{2}{3} - t \frac{3t - 2}{4} - \frac{2t + 3}{3} = \frac{2}{3} - t](https://tex.z-dn.net/?f=+%5Cfrac%7B3t+-+2%7D%7B4%7D+++-++%5Cfrac%7B2t+%2B+3%7D%7B3%7D++%3D++%5Cfrac%7B2%7D%7B3%7D++-+t)
Please Answer all ASAP
Answers
Answered by
1
Answer:
refer to the attachment above.!!!
hope it helps you:)
Attachments:
![](https://hi-static.z-dn.net/files/d80/06b8e5bef0df90c2e519d82e82c88723.jpg)
Answered by
17
2) 2y + 9 = 4
2y = 4–9
2y = –5
y = –5/2 = –2.5
3)t/5 = 10
t = 5×10
t = 500
5) 3(t – 3) = 5(2t + 1)
3t – 9 = 10t + 5
3t–10t = 9+5
–7t = 14
t = –2
6) 2x - 1 = 14 - x
2x–x = 15
x = 15
9) 4z + 3 = 6 + 2z
4z – 2z = 6–3
2z = 3
z = 1.5
10) 7x –9 = 16
7x = 16+9
7x = 25
x = 25/7 = 3.57
Similar questions